2003
DOI: 10.1583/1545-1550(2003)010<0531:tvtcsf>2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Two-Dimensional Versus Three-Dimensional CT Scan for Aortic Measurement

Abstract: Minor axis measurements on axial CT scan can substitute for diameters obtained from 3D reconstructions in most clinical situations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
12
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 26 publications
2
12
0
Order By: Relevance
“…We found that intraclass correlation coefficients for diameter and volume measurements were excellent, which indicates that one AAA measurement is likely sufficient for the follow-up of patients with AAA. The correlation coefficients found in our study are slightly better than those previously reported in the literature (13,15,16). This is most likely the result of our having specially trained dedicated 3D imaging technologists and confirms the results of a previous study that showed improvement of 3D laboratory measurements with increasing technologist experience (24).…”
Section: Predictive Value Of Diameter and Volume Changes For Appearansupporting
confidence: 86%
“…We found that intraclass correlation coefficients for diameter and volume measurements were excellent, which indicates that one AAA measurement is likely sufficient for the follow-up of patients with AAA. The correlation coefficients found in our study are slightly better than those previously reported in the literature (13,15,16). This is most likely the result of our having specially trained dedicated 3D imaging technologists and confirms the results of a previous study that showed improvement of 3D laboratory measurements with increasing technologist experience (24).…”
Section: Predictive Value Of Diameter and Volume Changes For Appearansupporting
confidence: 86%
“…1 Distortion in the axial image introduced by aortic tortuosity may be minimized by measuring the lesser diameter. 90 Interobserver variability is always higher than intraobserver variability, 91,92 suggesting that follow-up of aortic disease in a specific patient should be performed by a single experienced observer. 88,89 In summary, CTA is one of the most used techniques in the assessment of aortic diseases.…”
Section: F Ctmentioning
confidence: 99%
“…This measurement should be taken outer wall to outer wall in lateral and anteroposterior projection. There is still some controversy if measurement should be taken on axial slices or longitudinal reformation perpendicularly to aneurysm central line [70][71][72]. Then CTA will display the relation ship of AAA with renal, mesenteric and celiac arteries and aneurysm extension in iliac arteries.…”
Section: Abdominal Aortic Aneurysmmentioning
confidence: 99%